Modeling an Instrument for Measuring E-Learning use in Learning Processes Based on ISO/IEC 38500:2008 - Tridalestari, Ferra Arik; Prasetyo, Hanung Nindito (Jurnal Teknologi dan Manajemen, 2025)
In the context of E-Learning development, E-Learning technology is part of the Information Technology Governance System in higher education institutions. Sometimes, E-Learning   implementation is carried out, but administrators do not know whether learners are studying effectively and achieving educational goals, whether the platform provides the expected added value in the learning process, and whether the quality of learning has been achieved. Therefore, accurate and effective E-Learning measurement is necessary to ensure that the implementation quality aligns with IT governance objectives in higher education institutions. One strategic approach to measurement is using the ISO 38500 framework. The strategic components of ISO 38500 can serve as the foundation for developing E-Learning measurement instruments in higher education. By utilizing these measurement instruments, organizations can identify the strengths and weaknesses of their E-Learning system, enabling continuous improvements to enhance the quality of learning materials, teaching methods, and user experience (for both lecturers and students). The E-Learning measurement instrument, developed based on ISO 38500 indicators, provides valuable data and insights for managerial decision-making. Based on the measurement results, management can make informed decisions regarding budget allocation for further development, updates or enhancements to the E-Learning platform, and the creation of new learning content or more effective training strategies.